Impaired production of mononuclear cell procoagulant activity in chronic lymphocytic leukaemia. Issue 1 (January 1983) - Cortellazzo, S; Viero, P; Barbui, T; Colucci, M; Semeraro, N
Abstract : Chronic lymphocytic leukaemia (CLL) is associated with a low incidence of thrombotic complications, or disseminated intravascular coagulation (DIC), or both, despite the frequent occurrence of severe infections. We have investigated the capacity of blood mononuclear cells to produce procoagulant activity when stimulated with bacterial endotoxin in 16 patients with untreated chronic lymphocytic leukaemia (CLL). Procoagulant activity generated by patients' cells after prolonged incubation with endotoxin was significantly lower than that produced by cells from a matched control group (p less than 0.001). The defect could not be attributed to an inhibitory effect of leukaemic lymphocytes. It is suggested that in CLL the monocyte has an intrinsic functional abnormality of the procoagulant response to endotoxin and possibly to other stimuli. These findings help explain why CLL patients do not develop thrombotic complications despite the high incidence of severe infectious diseases.